Implementasi Akad Ijarah dalam Praktik Sewa Lahan Sawah dengan Sistem Pembayaran Setelah Panen - Adieb Hilal Hamdala; Popon Srisusilawati; Neng Dewi Himayasari (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Rice field leasing with a post-harvest payment system is a common agricultural practice in Buntu Village, Ligung District, Majalengka Regency. This study aims to examine the implementation of rice field leasing practices and analyze them from the perspective of Islamic law, particularly the ijarah contract. This research employs a qualitative method using normative-juridical and empirical approaches. Data were collected through interviews, observation, and documentation and analyzed descriptively based on fiqh muamalah theory. The results show that the leasing practice constitutes an ijarah contract because it involves the utilization of agricultural land by tenant farmers in exchange for an agreed rental payment. From the perspective of Islamic law, the practice fulfills the pillars and conditions of ijarah, including contracting parties, object of contract, rental payment, and consent expression. Although the rent is paid after harvest, the practice remains permissible as long as the rental value is clearly determined at the beginning and not tied to harvest yield. Abstrak. Praktik sewa-menyewa sawah dengan sistem pembayaran setelah panen merupakan bentuk muamalah yang berkembang di masyarakat Desa Buntu Kecamatan Ligung Kabupaten Majalengka. Penelitian ini bertujuan untuk mengetahui praktik sewa sawah tersebut serta menganalisisnya dari perspektif hukum Islam, khususnya akad ijarah. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan yuridis normatif dan empiris melalui pengumpulan data berupa wawancara, observasi, dan dokumentasi yang dianalisis secara deskriptif-analitis berdasarkan teori fikih muamalah. Hasil penelitian menunjukkan bahwa praktik sewa sawah di Desa Buntu merupakan akad ijarah karena terdapat pemanfaatan lahan oleh petani penggarap dengan imbalan sewa yang disepakati. Ditinjau dari hukum Islam, praktik tersebut telah memenuhi rukun dan syarat akad ijarah baik dari aspek subjek akad, objek akad, ujrah, maupun sighat akad.